The conduct of international enterprises in developing countries: An empirical review of some prejudices - Ehrenfried Pausenberger (Intereconomics, 1980)
Do multinational enterprises act in developing countries as a motive force for progress or do they perpetuate colonialism by different means? The fierce controversy on this question still continues, fuelled not only by basic ideological differences but by dearth of empirical evidence. Prof. Pausenberger is helping to overcome the lack of knowledge.
Keywords: 330; Multinational Corporations